Equilibrium Dominance in Experimental Financial Markets - Cadsby, Charles Bram; Frank, Murray; Maksimovic, Vojislav (Review of Financial Studies, 1998)
We examine the predictive power of equilibrium dominance in experimental markets where firms with investment opportunities have an informational advantage over potential investors and are permitted to purchase a money-burning signal. Equilibrium dominance often fails to predict well when a Pareto-superior sequential equilibrium is also available. Instead, equilibrium selection appears to be related to the potential earnings of a more valuable firm that can signal its type successfully by defecting from the sequential equilibrium. Potential investors formulate their bids for firm equity based primarily on expectations formed adaptively in response to signaling choices made by firms.